2017
DOI: 10.5005/jp-journals-10024-1986
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bacteriological Profile in the Apical Root Segment of the Patients with Primary Apical Periodontitis

Abstract: Introduction: Apical periodontitis usually results from bacterial accumulation and contamination occurring in the root-canal system, and extending beyond the apical foramen to involve the periapical tissues. Literature has a paucity of the studies that stress on the division and analysis of the pulp canal segments. The reason for this disparity might be the technique used for collecting the samples from the pulp canals. Hence, we carried out the present study to evaluate the microbial flora in the apical part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Based on the 16S rRNA technique, complex bacterial populations were reported present in AP individuals, mostly classified within phyla of Proteobacteria , Firmicutes , Bacteriodites , Fusobacteia , and Actinobacteria [12, 1623], where Proteobacteria , Firmicutes and Bacteriodites were always found prevalent. With 10 patients (10 extracted teeth) involved, Siqueira’s early study identified 187 phylotyes belonging to 84 genera and 10 phyla in apical root canal infections, where Proteobacteria and Firmicutes together occupied about two thirds of all sequences obtained [16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the 16S rRNA technique, complex bacterial populations were reported present in AP individuals, mostly classified within phyla of Proteobacteria , Firmicutes , Bacteriodites , Fusobacteia , and Actinobacteria [12, 1623], where Proteobacteria , Firmicutes and Bacteriodites were always found prevalent. With 10 patients (10 extracted teeth) involved, Siqueira’s early study identified 187 phylotyes belonging to 84 genera and 10 phyla in apical root canal infections, where Proteobacteria and Firmicutes together occupied about two thirds of all sequences obtained [16].…”
Section: Introductionmentioning
confidence: 99%
“…The final sample consisted of 21 studies (Figure 1). Ten studies investigated only primary infections (Baumgartner & Falkler, 1991; Dougherty et al., 1998; Ozok et al., 2012; Persoon et al., 2017; Rôças et al., 2010; Siqueira et al., 2009; Siqueira et al., 2011; Siqueira, Rôças, Alves, et al., 2004; Takahama et al., 2018; Tatikonda et al., 2017), 8 only posttreatment infections (Antunes et al., 2015; Pereira et al., 2017; Perez‐Carrasco et al., 2023; Ping et al., 2015; Siqueira et al., 2016; Siqueira et al., 2020; Subramanian & Mickel, 2009; Wang et al., 2012), and 3 included both types (Bouillaguet et al., 2018; Chugal et al., 2011; Qian et al., 2019). The search for grey literature using the Proquest database did not return any document related to the objective of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, the root apex specimens were triturated using orthodontic pliers (Pereira et al., 2017). As for the other studies, 5 used endodontic files and paper points (Baumgartner & Falkler, 1991; Chugal et al., 2011; Siqueira et al., 2009; Siqueira, Rôças, Alves, et al., 2004; Tatikonda et al., 2017) and 2 studies used only endodontic files (Bouillaguet et al., 2018; Dougherty et al., 1998) to take samples from the root canal in the resected apical root segment; in the other 2 studies, samples were obtained by agitation and centrifugation of the root specimens (Subramanian & Mickel, 2009; Wang et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations utilizing broad-range culture and 16S rRNA sequencing have identified a variety of relevant species into the microbial communities associated with necrotic root canals, primarily strict anaerobic bacteria from Peptostreptococcus, Prevotella, Porphyromonas, Fusobacterium, Eubacterium, and Actinomyces, along with facultative anaerobic Streptococci (Sakamoto et al, 2006;Tatikonda et al, 2017). Notably, the presence of these pathogens has been linked to primary apical periodontitis; whereas, secondary apical periodontitis exhibits distinct microbial populations, predominantly Gram-positive facultative anaerobes like Streptococcus, Lactobacillus, and Enterococcus (Siqueira and Roĉas, 2005;Siqueira et al, 2016;Qian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%